Modified digraphs method in the problem of authenticating users using keystroke dynamics - Алексеев, Василий Александрович; Синица, Юлия Александровна; Горелов, Денис Юрьевич (Ukrainian Information Security Research Journal, 2016)
Keystroke dynamics analysis is fairly fast growing direction of research that is due to need to ensure the security of a large park of applications and adaptation to the changing technologies. In this article proposed keystroke dynamics user authentication method which uses modified method of digraphs. In this case, it suggested the division of the keyboard keys on their functional purpose. Each zone generates its own events (double and single) which are analyzed separately. The final decision of authentication is made on the basis of all the data from all functional areas of the keyboard. For paired keyboard events is used the ratio of time parameters of digraphs. This makes it possible to analyze both static and dynamic features keystroke rhythms of a user. The main calculated parameter in a single event is hold time of key. Processing of such events gives the possibility to add unique additional user profile attributes. This integrated approach allows to improve the accuracy of authentication using keystroke dynamics without increasing the volume of data being processed.